Advancements in Aeromedical Management of Diabetes: Implications for Aviation Safety - Young Hwan Kwon (Hanggong uju uihakoeji)
The increasing prevalence of diabetes mellitus among aviation personnel poses significant challenges to flight safety, necessitating stringent aeromedical management. This study examines the current prevalence of diabetes in Korea’s aviation sector, analyzes associated health risks, and evaluates international guidelines from the International Civil Aviation Organization, the Civil Aviation Safety Authority, and the Federal Aviation Administration for managing diabetic aviation personnel. In 2022, diabetes was identified in 1.8% of aviation medical examinations in Korea, with prevalence increasing with age. The study highlights the critical importance of regular health assessments, blood glucose monitoring, and adherence to medical protocols to mitigate risks such as hypoglycemia and cardiovascular complications that could impair flight safety. By comparing international standards, the study underscores the need for comprehensive, evidence-based guidelines tailored to the Korean context to ensure the health of aviation personnel and the safety of flight operations.